Obesity and gastric balloon - Mohammed I Yasawy; Abdulaziz A Al-Quorain; Anas M Hussameddin; Zakia M Yasawy; Raid M Al-Sulaiman (Wolters Kluwer Medknow Publications, 2014)
Background: The obesity epidemic, which is among the most common nutritional disorders, is rising rapidly worldwide. It leads to several health problems such as metabolic disorders, stroke, and even cancer. Efforts to control obesity with exercise and diet have a limited value in obese patients and different approaches to do this have been tried. In this paper, we share our experience with bioenteric intragastric balloon (BIB) in treating obesity: Its safety, tolerability, and its efficacy in weight reduction. Materials and Methods: From January 2009 to September 2012, a total of 190 gastric balloons was inserted on patients at the endoscopy unit in King Fahd Hospital of the University, Al-Khobar. This is an evaluation of the first 100 patients. All the patients had a body mass index of over 30 kg/m 2 and were within the age range of 17-55 with a mean age of 32 years. After consent, preballoon investigation tests and anesthesia evaluation, BIB was inserted under monitored anesthesia care sedation in the endoscopy suite. The balloon was filled with 500-700 mls of stained saline. All patients' were given an analgesic and antiemetic for a week and antisecretory proton pump inhibitor's for 6 months. Diet and the importance of the exercise were part of the preballoon insertion phase and protocol. The balloon was removed after 6-12 months. Results: The weight loss response to BIB in the 100 patients are classified into four groups: In the uncooperative, noncompliant patients - the maximum weight loss was 7 kg, while in the most compliant patients the weight loss reached up to 39 kg. In addition, there was significant improvement into diabetes mellitus, hypertension, dyslipidemia, and fatty liveras. Its safety and tolerability were extremely acceptable. Conclusion: Our data indicates that in well-selected patients, BIB is an effective device, which with minimum complications helps to achieve body weight loss and resolve many obesity related morbidities in cooperative and dedicated obese patients.